Ayurveda in the Management of Avascular Necrosis of Femoral Head - A Case Report (International Journal of Ayurveda and Pharma Research, 2024)
Avascular necrosis (AVN) is defined as cellular death of bone components due to interruption of the blood supply. The bone structures then collapse, resulting in pain, loss of joint function and long-term joint damage. Treatment goals for AVN are to improve the joint, stop the bone damage, and ease pain. In modern science treatment includes NSAIDS, core decompression, bone grafting and total joint arthroplasty which have their own complications, high cost and prognosis is also very poor. In Ayurveda it can be correlated to the Asthi-Majja gatha vata. In this Raktavaha Srotorodha also occur which results in Asthi Dhatu Kshaya. Aim of study is to introduce an alternative therapeutic modality through Ayurveda which help to reduce pain, improve quality of life and prevent further damage of bone which is cost effective as well. The present case report is a single case study of a 32year old female patient who was diagnosed with Stage Ⅱ Avascular Necrosis of bilateral femoral head done at Government Ayurveda College Panchakarma Hospital, Poojappura, Thiruvananthapuram. She was treated with selected Panchakarma treatments and specific Samana oushadhis. There was significant improvement in the symptoms which was assessed using relevant tools like VAS score for pain, goniometer for range of movement and Oxford Hip score for assessment of function and pain in hip. The present case study documents that Panchakarma procedures and Samana oushadhis can be effective in AVN and improve the quality of life of patient.